Reclamation of irrigated sodic soil using millet chaff as an amendment - Nasidi, Nuraddeen Mukhtar; Wayayok, Aimrun; Sani, K. M.; Shanono, N. J.; Zakari, M. D. (Faculty of Engineering, Universiti Putra Malaysia, 2018)
The productivity of agricultural lands is known to gradually reduce when the salt continue to accumulate. Such salt accumulation is resulted from both underground intrusion and the excessive application of chemical fertilizer by the farmers. Following a preliminary study in the Thomas Irrigation Scheme, Kano, a larger proportion of the soil found to be sodic. Although, reclaiming such soil using chemical amendment found to be promising and economically viable in many places, but in some places it is not. An effort towards employing organic materials that are abundant and economically viable as amendments can help reclaim sodic soil thereby informing local farmers. Herein, we reported the outcomes of using Millet chaff as an organic amendment for reclaiming sodic soils. The experiment carried out in twelve plots out of which nine were treated with three different quantities of millet chaff (M1 = 680, M2 = 1,080 and M3 = 1,440 g/m2), whereas the remaining three were left as control (C) . A significant improvement in soil quality indicators were observed at the end of the experiment. Sodium adsorption ratios found to drastically reduce for M1 (0.66), M2 (0.76), M3 (0.42) as compared to C (8.10). The exchangeable sodium percentage are M1 (23.92%), M2 (28.46%), M3 (12.56%) as compared to C (76.82%). The least significant difference value (26.45) showed difference between M1 and M2 (32.955 mean difference) and M2 and M3 (34.778 mean difference) respectively. This showed that the M2 (1,080 g/m2) is statistically the best quantity. Results also showed that the application of amendment would be more effective when applied at least one month before planting to attain maximum decomposition of millet chaff. This process of soil organic reclamation is considered the most effective and efficient as the amendment is readily available, none hazardous, and it requires no high technical skills.